2017
DOI: 10.22491/1678-4669.20170025
|View full text |Cite
|
Sign up to set email alerts
|

Eyewitnesses memory for faces in actual criminal cases: An archival analysis of positive facial composites

Abstract: Facial composites are crucial in the criminal justice system. In this archival study, we investigated the assumption that the success of facial composites depends partly on variables related to the crime, which either impairs or facilitates mnemonic processes. When a facial composite is successful in taking an offender to court it is sometimes archived as a positive facial composite, including a photo of the culprit and information about the crime. A total of 88 positive facial composites were investigated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Most studies reported here were conducted with older, feature‐based composite systems. Clearly, similar studies with newer, holistic composite construction systems (e.g., Hancock, 2000; Saraiva et al, 2018; Skelton et al, 2019; Tredoux et al, 1999; Tredoux et al, 2006) are necessary to update our knowledge. Because witnesses may be repeatedly exposed to composites constructed by others, for example via television, the press, and social media, future studies should not only use different retention intervals, but also investigate repeated exposure.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Most studies reported here were conducted with older, feature‐based composite systems. Clearly, similar studies with newer, holistic composite construction systems (e.g., Hancock, 2000; Saraiva et al, 2018; Skelton et al, 2019; Tredoux et al, 1999; Tredoux et al, 2006) are necessary to update our knowledge. Because witnesses may be repeatedly exposed to composites constructed by others, for example via television, the press, and social media, future studies should not only use different retention intervals, but also investigate repeated exposure.…”
Section: Discussionmentioning
confidence: 93%
“…By publishing the composite, police investigators hope that a member of the public will recognize the person depicted and report this to the police (Davies & Valentine, 2007; Shepherd & Ellis, 1996). Face composites have been used by the police across the globe for many decades, from the US to Europe and Australia and many other countries, including Brazil, South Africa and in former socialist and communist countries (Saraiva et al, 2018; Schmidt & Tredoux, 2006; Shepherd & Ellis, 1996; Snetkow, Sinin, & Delang, 1981).…”
Section: Introductionmentioning
confidence: 99%